Entscheidungsträger im Internet (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
Social networks, payment services, gaming platforms - they all have sophisticated sets of rules governing the use of their services. Just as complex are the systems with which these private actors enforce their rules. Automated, human or hybrid decision-making structures are designed to provide efficient and equitable rule enforcement. Due to the high relevance of these platforms, current regulatory projects such as the Digital Services Act are attempting to establish clear rules for these private decision-making structures. This anthology gathers empirical and theoretical contributions that explore questions about institutionalization, legitimacy and consequences of this development. With contributions by RAin Dr. Bettina Bacher; Steliyana Doseva; Rita Gsenger, M.A.; Prof. Dr. Dirk Heckmann; Alexandra Keiner, M.A; Christoph König; Dr. Johanne Kübler; Ferdinand Müller; Amelie Röhling; Finn Schädlich; Jan Schillmöller; Prof. Dr. Hanna Schmid-Petri; Simon Schrör, M.A.; Dr. Ben Wagner and Johannes Weil.